PENERAPAN METODE MIND MAP PADA PEMBELAJARAN TEKS BERITA DI SMPIT MNU TRUCUK - Nur Wakhidah; Ferdian Achsani (CARAKA, 2019)
Learning methods are a set of strategies used in the learning process. learning methods are needed by teachers, to improve student competence in any particular sub-section or material. The use and use of learning methods must be adapted to the needs of the community and the suitability of the material to be taught. This research is included in the descriptive qualitative. Data collection techniques in this study are the measurement technique. Measurements were made on the ability of students to analyze the structure and elements of news text class VII SMP NU Trucuk, class VIII A, amounting to 12 students. The results showed that the application of the mind map method in learning to analyze the elements and structure of news text has benefits and obstacles in its application. The final results of applying this method can be said to be good. This can be seen from the final results of the calculation of the average value of 75.8.